The Strategy of Radar Data Integration Between Indonesia and Singapore as an Airspace Security System in the Riau Islands and Natuna - Santoso, Budi; Firman Z, Yanda Dwira; Aritonang, Sovian (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the strategy of radar data integration between Indonesia and Singapore to enhance the airspace security system in the Riau Islands and Natuna. The focus includes analyzing the implications of the Leaders Retreat 2022 policy, evaluating bilateral collaborative efforts, and formulating technology-based strategies for managing the Flight Information Region (FIR). This research adopts a Mixed Methods Sequential Explanatory approach, combining quantitative analysis of airspace violation data and qualitative analysis of policies and expert interviews. Quantitative data is processed using descriptive statistics, while qualitative data is analyzed using the constant comparative method. The study reveals that radar data integration improves the effectiveness of airspace surveillance, strengthens Air Sovereignty, and supports flight safety. Technology-based collaborative strategies, such as the use of advanced radar systems and integrated personnel training, are key to successful implementation. This research contributes new insights to the study of airspace security by proposing a radar data integration model that is responsive and adaptive to geopolitical dynamics in the strategic regions of the Riau Islands and Natuna.